MODEL PEMBELAJARAN GALLERY WALK PADA MATA PELAJARAN JURNAL KHUSUS PERUSAHAAN DAGANG DI SMAN 1 REJANG LEBONG - Sigit Marteja (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
This study is the application of the Gallery Walk model in improving student learning activities in accounting subjects of specialized journal material for trading companies in SMAN 1 Rejang Lebong. Retrieval of data using methods of observation, questionnaires, written tests and deeds ,. The study was conducted by the classroom action research (CAR) method. Data collection techniques using test and observation techniques. Quantitative and qualitative analysis techniques. The results of the study stated that there was an increase in students who were active from cycle 1, cycle 2 and cycle 3. Increased average learning outcomes followed by mastery learning. Cycle I achieved an average of 59.16 and students completing learning 45.83%, Cycle II achieved an average of 67.08 and students completing learning 54.16%, Cycle III achieved an average of 85.41 and students completing learning 100%. Learning Gallery Walk model can increase learning activities more vibrant both classical, group and individual.